Guidance condition correction into the design of two dimensional nanophotonic devices - Johnson, Steven G. (2012)
We quantify the importance of including finite thickness effects into the design of two dimensional nanophotonic metamaterial devices. Direct band diagram method and analytical guidance condition method are introduced and verified with nanostructured Lüneburg lens.